Scholarship status and gender differences in motivation among U. S. collegiate track and field athletes - Cremades, J. G.; Flournoy, B.; Gomez, C. B. (International Journal of Sports Science and Coaching, 2012)
The purpose of the current study was to determine differences in motivation between scholarship and non-scholarship collegiate male and female athletes. Participants (n = 162) were collegiate track and field athletes in the U. S. A. The Sport Motivation Scale (SMS) was used to assess participant's intrinsic and extrinsic motivation as well as amotivation. A 2 x 2 factorial MANOVA was used to determine scholarship status and gender differences. Significant main effects were found for scholarship status.